THE THE APPROACH TO THE SOLUTION MULTI - CRITERIA PROBLEMS OF OPTIMIZATION (MCIT: Proceedings of International scientific and practical conference, 2019)
A method for finding a compromise solving of multicriteria optimization problems with flexible limit constraints has been considered. The application of the method at simultaneous profit optimization and company’s revenue has been regarded.
Keywords: multicriteria optimization; technological matrix; compromise solving; flexible planning